IDENTIFICATION OF A LOCAL PROBIOTIC BACTERIUM USING 16S rRNA GENE SEQUENCE THAT WAS USED FOR FIELD TRIAL TO ENHANCED WHITELEG SHRIMP (Litopenaeus vannamei) SURVIVAL - Tb. Haeru Rahayu; Ketut Sugama (Indonesian Aquaculture Journal, 2015)
The use of local probiotics in the culture of aquatic organisms is increasing with the demand for more environmental-friendly aquaculture practices. The local bacterium isolate considered as a probiotic was added into the water of whiteleg shrimp (Litopenaeus vannamei) culture in a field trial. Four rectangular plastic ponds (ca. 20 m x 30 m per pond) were used for 100 days experimentation for six consecutive crops in two years experiment. Survival, harvest size, feed conversion ratio (FCR) and Vibrio bacterial count was compared with those of shrimp receiving and none of local isolate. Identification based on 16S rRNA gene sequence shown those isolate was Bacillus pumilus strain DURCK14 with 99% homology. Water shrimp pond added a local isolate had significantly higher survival at about 10.0% to 11.7% than shrimp without added the isolate (p<0.05), and better FCR, but no significant different in shrimp harvest size. Vibrio bacterial was undetected by total plate count. Moreover, it shown better projected yields on an annual basis (three crops per year).